2016
DOI: 10.1016/j.memsci.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pyrolysis conditions on gas separation properties of 6FDA/DETDA:DABA(3:2) derived carbon molecular sieve membranes

Abstract: A previously reported polyimide, 6FDA/DETDA:DABA(3:2), was pyrolyzed under different protocols to produce carbon molecular sieve (CMS) dense film membranes for separation of important gas pairs, including pure gases CO 2 /CH 4 , O 2 /N 2 and mixture gases 50% CO 2 /50% CH 4 and 50% C 3 H 6 /50% C 3 H 8. This study investigated the effects of pyrolysis temperature, O 2 doping, and precrosslinking on the separation performance of 6FDA/DETDA:DABA(3:2) CMS membranes. Comparing to the precursor membranes, separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(31 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…1 and 7 (45). Another study demonstrated that for different 6FDA-based polyimide precursors the same effect applies, and presumably is general to all CMS materials (46). While determination of the exact state of the oxygen is outside the scope of this current discussion, spectroscopic evidence of carbonyls has been previously reported (43); however one can envision a multitude of oxygen chemisorption pathways during the complex pyrolysis process.…”
Section: Gas Probesmentioning
confidence: 76%
“…1 and 7 (45). Another study demonstrated that for different 6FDA-based polyimide precursors the same effect applies, and presumably is general to all CMS materials (46). While determination of the exact state of the oxygen is outside the scope of this current discussion, spectroscopic evidence of carbonyls has been previously reported (43); however one can envision a multitude of oxygen chemisorption pathways during the complex pyrolysis process.…”
Section: Gas Probesmentioning
confidence: 76%
“…It suggests that the microstructure of CMSMs turns to more compact with increasing the pyrolysis temperature. This agrees well with the law in reports . By this means, the microstructure and gas permeability of resultant CMSMs can be tailored by pyrolysis temperature.…”
Section: Resultsmentioning
confidence: 61%
“…During the third stage, a large amount of small molecular gases would be released, such as H 2 , CO, CO 2 , O 2 , CH 4 , and NO X , resulting into the formation and evolution of the porous structure in membrane substrate ,. When the pyrolysis temperature goes up to 650 Ā°C, the TG curves become placid because of the alternation of predominantly thermal reaction from decomposition to poly(condensation) . The slight weight loss of precursor at the temperature above 650 Ā°C is due to the successively rearrangement and reorganization of the remaining membrane matrix.…”
Section: Resultsmentioning
confidence: 97%